Current power potential of a sea strait: The Bosphorus. (December 2017) - Ozturk, Mehmet; Sahin, Cihan; Yuksel, Yalcin
Abstract: The annual current energy potential of a sea strait, Bosphorus in Turkey, is evaluated by the calibrated and validated three dimensional numerical model results. The numerical approach is based on a number of unstructured flexible meshes (triangle or quadrilateral elements) and uses a cell-centered finite volume solution technique. Three-dimensional incompressible Reynolds averaged Navier-Stokes equations are solved invoking the assumptions of Boussinesq and hydrostatic pressure. The turbulence closure was implemented by using Smagorinsky and k- ε models in the horizontal and vertical domains, respectively. Water level and density differences acting on the model open boundaries combined with the meteorological structure of the region (wind speed, direction and atmospheric pressure difference) are the main forcing mechanisms of the numerical model as inputs. The strait flow is a typical example of a stratified flow among the world's straits, with a possible exception of having a negligible tidal oscillation. The results show that the complex geometry (both horizontally and vertically) of the strait combined with highly variable hydrological and meteorological conditions of the adjacent seas, the Marmara Sea and Black Sea, result in a considerable fluctuation in the kinetic energy potential. Cross-sectional variability of the kinetic energy is also notable both horizontally and vertically with increasing energy upwards and towards the shore. In spatial domain, although it is not the narrowest part of the strait, the highest kinetic energies are calculated at the southernmost part of the strait due to both a decrease in cross-sectional area and the presence of a sill on the bottom, a geometrical feature likely seen in straits that mainly control the flow structure (e.g., flow velocities). For a given cross section taken from a meandering part of the strait, the kinetic energy of the strait is higher at the outer and inner banks of the strait for the upper and lower layer flows, respectively. In time scale, the most energetic time period spans from the late spring to the end of summer related to the increase in water level difference between both ends of the strait due to long-term effects that represent seasonal variations (mainly the river inflows toward the Black Sea) and short-term effects (southward storms in the same direction with the upper layer flow). In winter, however, due to the southerly storms acting opposite to the surface layer flow, the kinetic energy potential of the strait drops to considerably low values occasionally. Highlights: Current power potential of a strait is evaluated with a 3D numerical flow model. Most energetic period is the period when barotropic forcing increases continuously. The highest energy potential occurs around regions where a sill is located. The outer bank of the meandering is more energetic than the inner bank. The depths close to surface have more energetic but less stable current pattern.